1993
DOI: 10.1128/aac.37.9.2030
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fluconazole and amphotericin B for treatment of experimental Candida endocarditis caused by non-C. albicans strains

Abstract: Amphotericin B and fluconazole were compared for the treatment of experimental Candida endocarditis caused by Candida tropicalis and C. parapsilosis. Rabbits received no therapy, amphotericin B (1 mg/kg of body weight per day intravenously), or fluconazole (100 mg/kg/day intraperitoneally) for either 11 or 21 days. Against both species, amphotericin B and fluconazole were equally effective overall; however, amphotericin B was more rapidly fungicidal than fluconazole in vivo against C. tropicalis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…However, although the serum levels were not tested, this possibility was contradicted by the fact that AmB was very effective at decreasing fungal densities in the kidneys. Moreover, previous studies using the same dosage of AmB in the endocarditis models also reported a very slow response of the infection (5,31,35,43,44).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, although the serum levels were not tested, this possibility was contradicted by the fact that AmB was very effective at decreasing fungal densities in the kidneys. Moreover, previous studies using the same dosage of AmB in the endocarditis models also reported a very slow response of the infection (5,31,35,43,44).…”
Section: Discussionmentioning
confidence: 98%
“…Controls receiving Cy alone at these same dosages were also included. AmB was given at a daily dose of 1 mg/kg as previously described (31,44).…”
Section: Methodsmentioning
confidence: 99%
“…A single colony of Candida obtained from a 24-h culture on Sabouraud dextrose agar (Cole-Parmer, Vernon Hills, IL) was grown in yeast nitrogen base (YNB) medium (Difco Laboratories, Detroit, MI) supplemented with 2% dextrose at 27°C for 24 h. Fibrin clots were prepared in sterile siliconized 1.5-ml tubes by combining 0.9 ml of human cryoprecipitate from volunteer donors (United Blood Services, Albuquerque, NM), 0.05 ml of aprotinin solution (Sigma, St. Louis, MO), and 0.05 ml of washed platelet-rich plasma suspension (ϳ10 8 platelets/ml diluted in 0.9% NaCl to provide approximately 250,000 to 300,000 platelets per g of vegetation mass). A fungal suspension was added to the preparation to achieve a starting inoculum of ϳ10 6 CFU/g, which corresponded to fungal densities recovered initially from previous rabbit endocarditis models (6,14,33). A sterile monofilament line (Pacifica Inc., Taipei, Taiwan) was inserted, and 0.1 ml of bovine thrombin (Jones Pharma Inc., Bristol, VA) was added.…”
Section: Methodsmentioning
confidence: 99%
“…The minimum inhibitory concentrations of the C. albicans strain were tested by e-test (AB Biodisk, Solna, Sweden). For in vivo experiments, the daily doses were 10 mg/ kg for fluconazole (21) and 1 mg/kg for amphotericin B (22,23) through intraperitoneal injection. Treatment or control (saline solution) doses were started immediately after the fungal instillation and for the following 2 days.…”
Section: Antifungal Treatmentmentioning
confidence: 99%